Legal and Socioeconomic Issues Concerning the Nigeria Higher Institution Loan Act 2023 - Aidonojie, Paul Atagamen; Obieshi, Eregbuonye; Inagbor, Michael; Ogbemudia, Ottah (JURNAL LEGALITAS, 2024)
The Nigeria Higher Institution Loan Act of 2023 serves as a pivotal framework for addressing financial accessibility to higher education. The Act's objectives center on providing interest-free loans to students for tuition fees and ensuring access to education for all Nigerians. However, despite the relevance of the Nigeria Higher Institution Loan Act of 2023 in addressing educational financial challenges, there seem to be legal and socioeconomic challenges generated by the said law. It is in this regard that this study adopts a hybrid method of study in examining the legal and socioeconomic issues inherent in the Nigeria Higher Institution Loan Act of 2023. Concerning this, 303 questionnaire were sent to respondents residing in Nigeria. A descriptive and analytical method was adopted in analyzing the result. The study found that the Act focused on ensuring loans reach those with genuine financial needs, but inadvertently excluded certain groups, raising questions of fairness. The requirement of guarantors, each meeting specific qualifications, adds another legal dimension to the Act and raises socioeconomic issues surrounding the accessibility of suitable guarantors. Furthermore, the Act underscores the importance of responsible loan management but also highlights the potential harshness of penalties, especially for economically disadvantaged borrowers. It was therefore concluded and recommended that the Higher Institution Loan Act of Nigeria brings together legal and socioeconomic elements, striving to provide financial accessibility to higher education while maintaining accountability. Evaluating and addressing these complex legal and socioeconomic issues is vital to ensure the Act fulfills its intended purpose of promoting equitable access to education for all Nigerians.